Challenges and opportunities in biogas conversion to microbial protein: A pathway for sustainable resource recovery from organic waste - Hafiz Muhammad Aamir Shahzad (6687767) (2024)
Addressing global food security is a paramount challenge that necessitates a shift towards enhanced food self-sufficiency. The escalating demand for animal-derived proteins, such as meat and dairy, underscores the critical role of livestock farming in meeting the nutritional needs of the global population. To sustain this, protein-rich feed, essential for livestock production, consumes a considerable share of agricultural resources. Concurrently, urban expansion significantly increases organic waste, undermining both economic and environmental sustainability. This highlights the urgent need for innovative waste management solutions that bolster sustainability. Microbial protein (MP), produced by methane-oxidizing bacteria (MOB), presents a promising solution. It offers a land-independent method for producing feed for livestock and aquaculture, potentially alleviating the pressure on agricultural lands. Despite its advantages, reliance on natural gas for MP production raises sustainability concerns when compared to traditional feeds like fishmeal and soybean meal. Recent research focuses on valorizing waste materials using high-protein microorganisms for animal feed production, thereby addressing these concerns. Aerobic fermentation of methane to produce MP, utilizing methanotrophic microbes, showcases distinct advantages. These microbes produce a protein-rich biomass, containing over 75% protein, offering a viable alternative to conventional protein sources. This review explores the potential of urban biowaste valorization for MP production through the integration of anaerobic digestion (AD) and subsequent fermentation of biogas. It delves into the valorization mechanisms of biogas from AD to MP, highlighting methane's value in MP production for environmental and economic sustainability. Despite advancements, challenges such as inefficient fermenters, MOB inhibition, and safety issues hinder large-scale MP production. Further investigation into the life cycle assessment (LCA) and techno-economic analysis (TCA) of these integrated technologies is essential for enhancing and establishing a sustainable MP production system. Other Information Published in: Process Safety and Environmental Protection License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.psep.2024.03.055